Micro pool characteristics of 316L and the influence of sulfur during SLM. (October 2021) - Kan, Xinfeng; Yin, Yanjun; Yang, Dengcui; Li, Wei; Sun, Jiquan
Highlights: Heat transport, liquid metal flow and solidification behavior in the molten pool are studied. Printing morphologies with different power and scanning speed parameter combinations are obtained. The model has taken into account the latent heat of phase transition, Marangoni effect and surface-active elements. Abstract: Selective Laser melting (SLM) is one of the important additive manufacturing (AM) methods, the process of which is very complex, involving multiple physical field coupling. In this paper, the finite volume method is used to simulate the SLM process, and the heat transport, liquid metal flow and solidification behavior in the molten pool are studied. The model has taken into account the latent heat of phase transition, Marangoni effect and surface-active elements. The time when the molten pool reaches a stable state is confirmed by the temperature of a probe point and the shape change of the main molten pool. Based on a successful SLM process parameter combination, the better process parameters are pursued according to the simulation results. The effect of the surface-active element sulfur on the shape of molten pool is explained from the perspective of the influence on the surface tension.